(untitled) - Cooke, Robert A. (Hoboken, N.J., 2005)
Most entrepreneurs interested in buying a business naturally assume they need large amounts of cash to work a deal. In fact, there are other ways to fund an entrepreneurial venture, particularly through seller financing. This simple, straightforward guide covers every possible source of financing available for wannabe business owners, how to deal with sellers, and how to use asset financing, selling equity, and asset protection. Buy Your Own Business with Other People’s Money shows that you don’t have to be rich to buy a business; you just need to be creative in financing your new business. For everyone who dreams of owning a business one day, this book has the answers.
Keywords: Business enterprises; Purchasing